THE IMPACT OF THE IMPLEMENTATION OF THE E-PERFORMANCE APPLICATION AND ADDITIONAL EMPLOYEE INCOME ON THE PERFORMANCE OF EMPLOYEES AT THE DEPARTMENT OF PUBLIC WORKS AND SPATIAL PLANNING - Christina Novalita Simanjuntak; Robert Tua Siregar; Elly Romy (JURNAL PROFIT, 2025)
This study aims to examine the effect of attendance, e-performance application, and employee income supplementation on employee performance. Quantitative paradigms and deductive reasoning were used in this study, developing a conceptual model based on previous empirical results and theoretical studies, which was then tested using structural equation modeling. The population in this study was the entire Public Works and Spatial Planning Agency of North Sumatra Province, totaling 985 employees. The sample was determined using the Slovin formula, resulting in a total of 169 respondents. Data were collected using a questionnaire in the form of a Google Form. The data collected in this study were analyzed using the PLS-SEM-based structural equation modeling method, which is a form of structural modeling to explain the patterns of relationships between variables, both directly and partially, and also to test the conceptual framework proposed in the study. The results showed that all proposed hypotheses were accepted. Attendance, e-performance, and employee supplementary income significantly impact employee performance at the Public Works and Spatial Planning Agency of North Sumatra Province, directly or partially.